Overview of non-epithelial ovarian tumours: Incidence and survival in the Netherlands, 1989–2015. (September 2019) - van der Hel, O.L.; Timmermans, M.; van Altena, A.M.; Kruitwagen, R.F.P.M.; Slangen, B.F.M.; Sonke, G.S.; van de Vijver, K.K.; van der Aa, M.A.
Abstract: Introduction: About 5% of ovarian tumours have a non-epithelial histology, including germ cell tumours (GCTs), sex cord-stromal tumours (SCSTs) and sarcomas. Because these non-epithelial ovarian tumours are rare and population-based studies are scarce, the aim of this population-based study is to describe trends in the incidence, treatment and survival of women with these tumours in the Netherlands. Methods: All women diagnosed with non-epithelial ovarian malignant tumours in the Netherlands between 1989 and 2015 were identified from the Netherlands Cancer Registry. Data on demographics, tumour characteristics and initial treatment were collected, and overall survival was analysed. Results: A total of 1258 non-epithelial ovarian tumours were identified comprising 752 GCTs (60%), 341 SCSTs (27%) and 165 sarcomas (13%). The European age-standardised incidence rate (ESR) was 0.4 per 100, 000 persons per year for GCTs, 0.2 for SCSTs and 0.1 for sarcomas. Approximately 97% of patients underwent surgical resection for the primary tumour, 31% received systemic treatment and 3% radiotherapy. Between the late 1980s and 2015, five-year overall survival improved for all histologic subtypes: GCTs rose from 73% to 88% (p = 0.03), SCSTs from 64% to 81% (p = 0.57) and sarcomas from 20% to 29% (p = 0.14). Conclusion: Malignant GCTs and SCSTs are rare, and their incidence has not significantly changed over recent decades. They have a good prognosis, which also improved slightly during this period. Primary sarcomas of the ovary are extremely rare and still have a poor prognosis. Highlights: Malignant germ cell tumours and sex cord-stromal tumours of the ovary are rare. Incidence did not significantly change during the last few decades in the Netherlands. Prognosis is good and improved slightly. Women with primary sarcomas of the ovary are extremely rare and have poor prognosis.